Island‑to‑Island Translations in the Contemporary Literary Capitalocene: Navigating the Politics of In/Visibility and Discoverability - Saint‑Loubert, Laëtitia (Mémoires du livre / Studies in Book Culture, 2025)
Drawing on professional experiences as a literary translator seeking to promote transversal, island‑to‑island translation flows, together with a comparative analysis of the contemporary literary ecosystems of the insular Caribbean and the Indian Ocean, this article pits recent debates on the issue of in/visibility in Translation Studies against concrete examples of translations marketed for English‑ and French‑speaking readers. In particular, it focuses on the recent co‑translation, for the Irish/UK market, of Reunionese writer Gaëlle Bélem’s debut novel, Un monstre est là, derrière la porte, and on the translation, for the French/Antillean market, of Trinidadian writer Elizabeth Nunez’s memoir, Not For Everyday Use. It highlights patterns present behind the concept of “book discoverability” to examine issues of asymmetry and invisibilization at work in the contemporary “literary Capitalocene,” and concludes with a call for a new book order in which translation can be (re)envisaged beyond the (neo)colonial doctrines of visibility and discovery.